2H-pyranone and isocoumarin derivatives from the endophytic fungus Pestalotiopsis microspora SC3082 derived from Scaevola taccada (Gaertn.) Roxb. Issue 21 (2nd November 2021) - Liao, Guangfeng; Wu, Ping; Liu, Zhanfeng; Xue, Jinghua; Li, Hanxiang; Wei, Xiaoyi
Abstract: Two new 2 H -pyranones (1 and 2 ), two new isocoumarins (4 and 5 ), and two known compounds (3 and 6 ) were obtained from solid cultures of the endophytic fungus Pestalotiopsis microspora SC3082. Their structures and revision of the absolute stereochemistry of 6 were established by spectroscopic analyses and computational calculations. Compounds 2, 4 and 6 displayed moderate antifungal activities against Candida albicans ATCC 10321 with MIC values of 25.0, 25.0, and 12.5 μg/mL, respectively. Graphical Abstract: